Cardiotoxicity from neoadjuvant targeted treatment for breast cancer prior to surgery - Liu, Yihua; Zheng, Li; Cai, Xingjuan; Zhang, Xiaojun; Ye, Yang (Frontiers in Cardiovascular Medicine, 2023)
Cancer treatment has been gradually shifting from non-specific cytotoxic agents to molecularly targeted drugs. Breast cancer (BC), a malignant tumor with one of the highest incidence worldwide, has seen a rapid development in terms of targeted therapies, leading to a radical change in the treatment paradigm. However, the use of targeted drugs is accompanied by an increasing rate of deaths due to non-tumor-related causes in BC patients, with cardiovascular complications as the most common cause. Cardiovascular toxicity during antitumor therapy has become a high-risk factor for survival in BC patients. Targeted drug-induced cardiotoxicity exerts a wide range of effects on cardiac structure and function, including conduction disturbances, QT interval prolongation, impaired myocardial contractility, myocardial fibrosis, and hypertrophy, resulting in various clinical manifestations, e.g., arrhythmias, cardiomyopathy, heart failure, and even sudden death. In adult patients, the incidence of antitumor targeted drug-induced cardiotoxicity can reach 50%, and current preclinical evaluation tools are often insufficiently effective in predicting clinical cardiotoxicity. Herein, we reviewed the current status of the occurrence, causative mechanisms, monitoring methods, and progress in the prevention and treatment of cardiotoxicity associated with preoperative neoadjuvant targeted therapy for BC. It supplements the absence of relevant review on the latest research progress of preoperative neoadjuvant targeted therapy for cardiotoxicity, with a view to providing more reference for clinical treatment of BC patients.